Strategi Dakwah Organsasi Syarikat Islam dalam Optimalisasi Penanganan Kenakalan Remaja di Kabupaten Bandung - Aulia Rihadatul Aisy, Tazkia; Mujib, Abdul (Ilmu Dakwah: Academic Journal for Homiletic Studies, 2015)
Juvenile delinquency that occurs in Syarikat Islam is a teenager who is affected by economic factors so that teenagers who should be enthusiastic about learning for the future must be cut off because of economic factors, besides that wrong association such as having free sex, underage thugs and motorcycle gangs that endanger other people. The purpose of this study was to find out the Da'wah Strategy Method, the implementation and the results obtained in dealing with unwanted juvenile delinquency in the Syarikat Islam environment. The method used is descriptive method with a quantitative approach. The results of the study show that: da'wah strategies through the socialization method, strengthen brotherhood through online (WhatsApp) or in person; As for the implementation, using the tadarus method aims to make the congregation understand the content of the Qur'an which is the guideline for Yaumil Akhir; and the results obtained Using the lecture method to convey da'wah with interesting studies or theories so that it is in great demand by young people who are currently attracted by western culture.